Актуальні питання корпоративного управління - Березянко, Тамара Володимирівна (My University, 2020)
Дана стаття відкриває цикл публікацій на тему особливостей корпоративного управління в сучасних умовах, що поєднують олігопольну специфіку національного ринку, сталу невирішеність ключових завдань корпоративного управління як системи, відсутність узгодженості між потребами розвитку суспільства та клановими інтересами провідних власників. Означена специфіка проявляється у збереженні недоліків корпоративного управління, консервації кептивних засобів вирішення майнових конфліктів, не розумінні необхідності відмінностей корпоративного управління в приватних та державних структурах, збереженні офшорних інструментів управління та анти суспільного менеджменту. Головним джерелом збереження та накопичення проблем в національному корпоративному управління вважаємо хибну теоретичну конструкцію, яку запозичено без урахування стратегічних економічних та соціальних пріоритетів країни. Накопичення проблем в управлінні корпораціями призводить до посилення провалів національного ринкового простору, що сприяє перетворенню загальної економічної кризи у кризу соціальну та суспільну. This article opens a series of publications on the peculiarities of corporate governance in modern conditions, combining the oligopolistic specifics of the national market, the constant unresolved key tasks of corporate governance as a system, lack of coherence between the needs of society and clan interests of leading owners. This specificity is manifested in the preservation of shortcomings of corporate governance, conservation of captive means of resolving property conflicts, failure to understand the need for differences in corporate governance in private and public structures, preservation of offshore management tools and anti-social management. We consider the main source of preservation and accumulation of problems in the national corporate governance to be a wrong theoretical construction, which is borrowed without taking into account the strategic economic and social priorities of the country. The accumulation of problems in corporate governance leads to increased failures of the national market space, which contributes to the transformation of the general economic crisis into a social and societal crisis. Differences in the system of corporate governance within the bipolar world do not allow to reach a final settlement of this issue. Тhe greater the level of concentration in the industry and the higher the power of the cartel, the greater the level of losses to society as a whole. The problem of influencing the behavior of oligopolistic players is manifested in 3 characteristic strategies: positioning of players in relation to the types of world politics; implementation of institutional policy through the behavior of players; changes in the negotiating practice of states under the influence of business players who realize their own aspirations through institutions. As you know, the strategy and system of corporate governance is a reflection of the market structure of society. According to many experts at the international and national level, crises are born in the slums of the corporate sector, are realized through the system of corporate governance and management and must be overcome in this area.
Keywords: society; oligopoly; економічна криза; корпоративне управління; суспільство; соціум; олігополія; corporate governance; economic crisis; socium; кафедра економіки праці та менеджменту